The role of critical literacy in citizenship education - Delgado-Rojas, Helen E. (2022)
The present text analyzes the connection between critical literacy and citizenship education. Its objective is to describe the theoretical concepts found in the rol it has in citizen education. It was found that the critical literacy approach should be considered in order to foster responsible participation and social transformation since it allows students to have a toolbox to confront social inequities. Furthermore, educational proposals have been put forward to take the theory to the praxis. Lastly, it is essential to bear in mind this information so as to prepare students for the challenges in the 21st century and provide education for social change.